KNOWLEDGE, ATTITUDE AND PRACTICES REGARDING SURGICAL SITE INFECTION PREVENTION AMONG STAFF NURSES IN SIR GANGARAM HOSPITAL, LAHORE - SHAHZADI , A; ANWAR , T; SONIA , . (Biological and Clinical Sciences Research Journal, 2024)
Surgical site infections (SSIs) are a significant contributor to healthcare-associated infections, leading to increased morbidity and prolonged hospital stays. Effective prevention strategies rely on healthcare professionals’ knowledge, attitudes, and practices (KAP), particularly among nurses directly involved in patient care. Objective: To assess the knowledge, attitudes, and practices regarding SSI prevention among staff nurses at Sir Ganga Ram Hospital, Lahore. Methods: A descriptive cross-sectional study was conducted among 120 nurses using a pre-validated structured questionnaire. Data were analyzed using SPSS version 26, with results presented as frequencies and percentages. Results: The majority of nurses (85%) had adequate knowledge about SSIs, with high awareness of blood sugar control (83.3%) and aseptic techniques (80.8%). Positive attitudes were prevalent, with 81.9% scoring well, and most participants agreeing on the importance of sterile materials (98.3%) and frequent dressing changes (92.5%). Adherence to good practices was noted in 87.7% of nurses, particularly in areas like skin preparation with alcohol and chlorhexidine (90%). However, gaps were identified in knowledge of specimen collection methods (64.2%) and in organizing training sessions for SSI prevention (25%). Conclusion: Nurses at Sir Ganga Ram Hospital demonstrated good KAP regarding SSI prevention, but gaps in specific practices highlight the need for targeted training and systemic improvements. Enhanced education and resource allocation can improve adherence to evidence-based guidelines, ultimately reducing the burden of SSIs in healthcare settings.